The main topic around the birth of academic start-up: a selective review - Reina, Rocco; Vesperi, Walter (Piccola Impresa / Small Business, 2018)
The role of Intellectual Capital has become increasingly important in the modern competitive system. The main objective of this study is to analyse the role and the relationship between Intellectual Capital and academic entrepreneurship. The Intellectual Capital in the Universities - created or existent - is not capable by itself to generate new entrepreneurship. For this reason, it is necessary to understand all the changes that the Intellectual Capital undertakes to become entrepreneurship. The final aim of this research is to understand how Intellectual Capital is changed over time during the process of creation of new academic entrepreneurship. The used methodology is divided in two phases. In a first phase we proceed to an analysis of the literature; in the second phase, we will attempt to theorize the main aspects of the relationship between IC and academic entrepreneurship. The outcomes of this study have different implications. First of all the results will help the university to better manage the process of exploitation of the Intellectual Capital produced through the spin-off creation. At the same time, the findings can help the external actors of the university to understand the business opportunities based on Intellectual Capital and competitive advantage in the market.